PEMASARAN ONLINE MEDIA PENUNJANG PERKEMBANGAN UKM BERBASIS PELATIHAN - Emaya Kurniawati; Sri Yuni Widowati; Aprih Santoso (Universitas YPPI Rembang, 2021)
PKM aims to provide counseling on business management in the marketing sector, especially the online marketing of SME products in Pedurungan Tengah Village, Semarang, so that their products are better known to the wider market. The main problem of partners is that they have not been able to market their products optimally and reach a wider market and they also do not know the importance of being online for a product marketing. The solution offered is the provision of counseling regarding business management in the field of marketing, especially the marketing of SME products online, so that business operations can take place. perfect. This is proven by the enthusiasm of the extension partners in participating and discussing (including the question and answer process) regularly during the online marketing of SME products.Keywords: SME, Marketing, Online and Product